2012
DOI: 10.1159/000341742
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Measurement of the Small Airways

Abstract: Noninvasive physiological measurements are reviewed that have been reported in the literature with the specific aim being to study the small airways in lung disease. This has mostly involved at-the-mouth noninvasive measurement of flow, pressure or inert gas concentration, with the intent of deriving one or more indices that are representative of small airway structure and function. While these measurements have remained relatively low-tech, the effort and sophistication increasingly reside with the interpreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 226 publications
(123 reference statements)
2
48
0
Order By: Relevance
“…Studies by Dellacá et al [30,31,32] indicate that changes in Xrs5Hz may reflect the number and distribution of choke points along the bronchial tree. Based on this concept, we hypothesize that the bronchodilator reduced the number of choke points and consequently reduced the airflow limitations in our patients [33]. …”
Section: Reactive Properties Of the Respiratory Systemmentioning
confidence: 99%
“…Studies by Dellacá et al [30,31,32] indicate that changes in Xrs5Hz may reflect the number and distribution of choke points along the bronchial tree. Based on this concept, we hypothesize that the bronchodilator reduced the number of choke points and consequently reduced the airflow limitations in our patients [33]. …”
Section: Reactive Properties Of the Respiratory Systemmentioning
confidence: 99%
“…FVC has been used as an indirect indicator of small-airway function, where an improvement in FVC may indicate a reduction in airway closure and air trapping [3]. In the Severe Asthma Research Program, Sorkness et al [93] observed marked physiological air trapping in the cohort with severe asthma (n = 287) compared to the non-severe asthmatics (n = 383), with a significant increase in RV, TLC, functional residual capacity and the RV/TLC ratio as a percentage of predicted values in the severe asthmatics.…”
Section: Clinical Relevance Of Small-airway-targeted Therapymentioning
confidence: 99%
“…From the previous articles in this current Thematic Review Series in Respiration , the authors have described that pathological, immunological and structural abnormalities occur in the small airways of patients with asthma and chronic obstructive pulmonary disease (COPD); that these abnormalities contribute to the physiological observations of the small airways being the major site of airflow limitation, and that small airways are involved in the clinical expression of these diseases [1,2,3]. Involvement of the small airways has been observed not only in patients with severe asthma [4], but also in those with mild disease [5,6] and in patients with nocturnal and exercise-induced asthma [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the characterisation of asthma and smoking-induced lung disease can also benefit from lung function and ventilation distribution indices that are thought to be sensitive to two distinct but sometimes concomitant phenomena: peripheral airway abnormality and abnormal heterogeneity of airway function at all lung depths. Hence, clinical research studies regularly include indices dedicated to represent peripheral and heterogeneous airway function [3]. Abnormality of these lung function indices can sometimes be assessed by comparison with reference values, either obtained for a particular index obtained in one study population [4,5] or based on reference equations constructed from the summary of previous equations [6].…”
Section: Introductionmentioning
confidence: 99%